HUBUNGAN POLA MAKAN ANAK TERHADAP TINGKAT KEJADIAN KARIES RAMPAN DI KELURAHAN KAMPUNG JAO KOTA PADANG - Zieta Sakinah Emdi; Defriman Djafri; Hidayati Hidayati (Andalas Dental Journal, 2017)
Based on Riskesdas 2013, dental caries is the main oral health problem that found in communities. Caries also occurs in the primary teeth, known as rampant caries. Cariogenics diet pattern will affect the accumulation of plaque which can cause rampant caries. This research used observational analysis with cross-sectional design study. Samples of this study are 57 students at pre-school in Kampung Jao District Padang City. The data was collected through questionnaires and oral examination, statistical analysis is using Chi-Square test analysis. There was significant relationships between the childrens diet patterns with the case of rampan caries in Kampung Jao District Padang City (p = 0.044). It is suggested to parents to steer and control the types and frequency of food and beverages consumed in children.